PHYTOCHEMICAL ANALYSIS OF SEVERAL CULTIVARS OF ARONIA MELANOCARPA FROM THE COLLECTION OF THE "ALEXANDRU CIUBOTARU" NATIONAL BOTANICAL GARDEN (INSTITUTE) - Ion Roșca; Aliona Glijin; Nina Ciorchină; Elisaveta Onica; Maria Tabăra; Alina Cutcovski-Muștuc; Tudor Ralea; Nina Zdioruc (Agricultura)
The purpose of this research included the quantitative determination of some biochemical compounds (ascorbic acid, reducing sugars, tannins, titratable acidity and phenolic compounds) from the fruits of three cultivars of Aronia melanocarpa from the collection of the "Alexandru Ciubotaru" National Botanical Garden (Institute). The quantitative determination of ascorbic acid in the frozen fruits of the three cultivars of black chokeberry demonstrated close values (28.1 and 27.2 mg / 100 g) in the fruits of the cultivars ˈNeroˈ and ˈAlecsandrinaˈ and significantly lower (23.8 mg / 100 g ) in those of the cultivar 'Viking'. The minimum and maximum contents of reducing sugars were recorded in the same cultivars – ˈNeroˈ (7.10%) and 'Viking' (6.68%), and those of the cultivar ˈAlecsandrinaˈ showed a value very close to the average (6.83%). The established titratable acidity had values between 0.854% and 0.955% malic acid and between 0.816% and 0.912% citric acid, and the maximum index of this parameter was recorded by the fruits of the cultivar ˈAlecsandrinaˈ. The quantification of tannins highlighted the fruits of the cultivar ˈNeroˈ, which was characterized by the maximum content of tannins (3.118%), exceeding by more than 48% the minimum value (2.079%) detected in the fruits of the cultivar ˈAlecsandrinaˈ. The quantitative biochemical study of phenolic compounds revealed a high content of these biologically active substances in the fruits of all cultivars investigated, and their maximum value (3202.7 mg GAE / 100 g d.m.) was recorded by the fruits collected from the cultivar 'Viking'.